2015
DOI: 10.3389/fnhum.2015.00495
|View full text |Cite
|
Sign up to set email alerts
|

Altered connectivity of the dorsal and ventral visual regions in dyslexic children: a resting-state fMRI study

Abstract: While there is emerging evidence from behavioral studies that visual attention skills are impaired in dyslexia, the corresponding neural mechanism (i.e., deficits in the dorsal visual region) needs further investigation. We used resting-state fMRI to explore the functional connectivity (FC) patterns of the left intraparietal sulcus (IPS) and the visual word form area (VWFA) in dyslexic children (N = 21, age mean = 12) and age-matched controls (N = 26, age mean = 12). The results showed that the left IPS and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 92 publications
(132 reference statements)
2
36
0
Order By: Relevance
“…It is widely accepted that reading involves multiple brain regions, including the frontal lobe, parieto‐temporal regions and occipito‐temporal regions (Epelbaum et al, ; Hoeft et al, ; Hoeft et al, ; Shaywitz & Shaywitz, ). Compared to typical readers, people with dyslexia normally exhibit an atypical pattern of brain activity across distributed brain regions (Brambati et al, ; Cohen et al, ; Cohen & Dehaene, ; Dehaene & Cohen, ; Paulesu, Danelli, & Berlingeri, ; Price & Devlin, ; Shaywitz et al, ) as well as abnormal functional connectivity among reading‐related brain regions (Boets et al, ; Horwithz, Rumsey, & Donohue, ; Paulesu et al, ; Pugh et al, ; Schurz et al, ; Zhou, Xia, Bi, & Shu, ).…”
Section: Introductionmentioning
confidence: 99%
“…It is widely accepted that reading involves multiple brain regions, including the frontal lobe, parieto‐temporal regions and occipito‐temporal regions (Epelbaum et al, ; Hoeft et al, ; Hoeft et al, ; Shaywitz & Shaywitz, ). Compared to typical readers, people with dyslexia normally exhibit an atypical pattern of brain activity across distributed brain regions (Brambati et al, ; Cohen et al, ; Cohen & Dehaene, ; Dehaene & Cohen, ; Paulesu, Danelli, & Berlingeri, ; Price & Devlin, ; Shaywitz et al, ) as well as abnormal functional connectivity among reading‐related brain regions (Boets et al, ; Horwithz, Rumsey, & Donohue, ; Paulesu et al, ; Pugh et al, ; Schurz et al, ; Zhou, Xia, Bi, & Shu, ).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, an increasing number studies using resting‐state fMRI have demonstrated that these overlapping brain regions are functionally connected to regions involved in reading and visual attention (Koyama et al., 2010; Vogel, Miezin, Petersen, & Schlaggar, 2012; Zhou et al., 2015). As reported by Zhou et al.…”
Section: Discussionmentioning
confidence: 99%
“…As reported by Zhou et al. (2015), the middle part of the prefrontal gyrus, the MFG, is functionally connected to seeds of the IPS and visual word form area (VWFA), which were selected on the basis of eye movement and word reading research, respectively. They found that the strengths of these functional connections were positively correlated with the naturalistic reading score but not with the word reading score, suggesting that the MFG is crucial in naturalistic reading.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduction in functional synchronization among reading-related brain areas (e.g., left temporoparietal, occipital-temporal, and inferior frontal cortices) has also been observed in individuals with RD. Such disconnections exist not only during reading-related tasks (Aboud, Bailey, Petrill, & Cutting, 2016;Finn et al, 2014;Paulesu et al, 1996) but also at rest (Koyama et al, 2013;Schurz et al, 2014;Zhou, Xia, Bi, & Shu, 2015), regardless of whether receiving intervention or not (Davis et al, 2010;Koyama et al, 2013).…”
Section: Functional and Structural Connectivity Anomalies In Rdmentioning
confidence: 99%